Seasonal Variability in The Genus-Family Structure of Free-Living Nematode Communities in Organic Shrimp Farming Ponds, Ca Mau Province - Thai, Tran Thanh; Quang, Ngo Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 3DO - 10.25073/2588-1140/vnunst.4864, 2019)
This study determined the seasonal variability of free-living nematode communities structure (genus/family level) in organic shrimp farms ponds in Tam Giang commune, Nam Can district, Ca Mau province. Based on the result of SIMPER analysis, the average similarity in nematode communities at genus level was low with 30.75% and 30.81% (in dry and rainy season, respectively). However, the average dissimilarity between seasons was considerably high with 71.75%. Terschellingia , Daptonema , and Parodontophora were main genera contributing to similarity/dissimilarity between seasons. At the family level, results of SIMPER analysis showed that the average similarity was low with 37.12% and 39.02% (dry and rainy, respectively). Additionally, the average dissimilarity between dry and rainy season was reasonably high with 64.06%. Specifically, four families such as Linhomoeidae, Xyalidae, Axonolaimidae, and Chromadoridae were the main families contributing to similarity/dissimilarity between seasons. Differences in sediment environmental characteristics between dry and rainy season are the reason for dissimilarity in the nematode communities structure. The high abundance of genus Terschellingia , Daptonema , Parodontophora may be indicative of organic enrichment conditions in shrimp pond sediment in both seasons. Nematodes with their rapid adaptation to changing environments can be used as a potential tool for bio-indicator. Keywords Bio-indicator, Ca Mau province, nematode communities, organic shrimp farms ponds, simper analysis. References [1] F. Y. Lin, A. H. Vo, V. B. Phan, T.T. Nguyen, D. Bryla, C.T. Tran, J.B. Robbins, The epidemiology of typhoid fever in the Dong Thap Province, Mekong Delta region of Vietnam, The American journal of tropical medicine and hygiene 62 (5) (2000) 644-648. [2] F. Semprucci, M. Moreno, S. Sbrocca, Rocchi M, G. Albertelli, M. Balsamo, The nematode assemblage as a tool for the assessment of marine ecological quality status: a case-study in the Central Adriatic Sea, Mediterranean Marine Science 14 (1) (2013) 48-57. [3] Q.X. Ngo, N.C. Nguyen, D.T. Vanreusel, A., Distribution pattern of free living nematode communities in the eight Mekong estuaries by seasonal factor, Journal of Vietnamese Environment 4 (1) (2013) 28-33. [4] C. Heip, M. Vincx, G. Vranken, The ecology of marine nematodes, Oceanography and Marine Biology: An Annual Review 23 (1985) 399-489. [5] M. Hodda, W.L. Nicholas, Nematode diversity and industrial pollution in the Hunter River Estuary, NSW, Australia, Marine Pollution Bulletin 17 (1986) 251-255. [6] D.M. Alongi, Intertidal zonation and seasonality of meiobenthos in tropical mangrove estuaries, Marine Biology 95 (1987) 447-458. [7] C. Tudorancea, A. Zullini, Associations and distribution of benthic nematodes in the Ethiopian Rift Valley lakes, Hydrobiologia, 179 (1) (1989) 81-96. [8] M. Hodda, W.L. Nicholas, Production of meiofauna in an Australian estuary, Wetland 9 (1990) 41-48. [9] S. Beier, W. Traunspurger, Seasonal distribution of free-living nematodes in the Körsch, a coarse-grained submountain carbonate stream in southwest Germany, Nematology 5 (4) (2003) 481-504. [10] M. Hourston, I.C. Potter, R.M. Warwick, F.J. Valesini, K.R. Clarke, Spatial and seasonal variations in the ecological characteristics of the free-living nematode assemblages in a large microtidal estuary, Estuarine, Coastal and Shelf Science 82 (2) (2009) 309-322. [11] T.T. Tran, T.L. Pham, T. Nguyen, X.Q. Ngo, Relationship of free-lingving nematode communities to some environmental characteristics in the organic shrimp farms, Ca Mau province, Vietnam Journal of Science and Technology 56 (5) (2018). [12] T.T. Tran, T. M. Y. Nguyen, T. Nguyen, X.Q. Ngo, Meiofauna in the mangrove–shrimp farms ponds, Ca Mau province, Vietnam Journal of Science and Technology 55 (3) (2017) 271. [13] E. A. El Hag, Food and food selection of the Penaeid prawn Penaeus monodon (Fabricius), In Limnology and Marine Biology in the Sudan, Springer Netherlands (1984) 213-217. [14] V. C. Chong, A. Sasekumar, Food and feeding habits of the white prawn Penaeus merguiensis, Marine ecology progress series 5 (20) (1981) 185-191. [15] Nguyen Thi My Yen, Tran Thanh Thai, Nguyen Tan Duc, Ngo Xuan Quang, Free living nematode communities as fundamental food for shrimps in the ecological - model of mangrove - shrimp farming ponds, Nam Can district, Ca Mau province, Vietnam Journal of Biotechnology, 16 (3) (2018) 581 -588. [16] K.R. Clarke, R.N. Gorley, PRIMER v6: User Manual/Tutorial PRIMER-E: Plymouth (2006). [17] J. Ingels, A.V. Tchesunov, A. Vanreusel, Meiofauna in the Gollum Channels and the Whittard Canyon, Celtic Margin-how local environmental conditions shape nematode structure and function, PLoS One 6 (5) (2011) e20094. [18] L. Cai, S. Fu, J. Yang, X. Zhou, Distribution of meiofaunal abundance in relation to environmental factors in Beibu Gulf, South China Sea, Acta Oceanologica Sinica 31 (6) (2012) 92-103. [19] X. Q. Ngo, N. Smol, A. Vanreusel, The meiofauna distribution in correlation with environmental characteristics in 5 Mekong estuaries, Vietnam, Cahiers de Biologie Marine 54 (2013) 71 -83. [20] B. Górska, K. Grzelak, L. Kotwicki, C. Hasemann, I. Schewe, T. Soltwedel, W. łodarska-Kowalczuk, M., Bathymetric variations in vertical distribution patterns of meiofauna in the surface sediments of the deep Arctic ocean (HAUSGARTEN, Fram strait), Deep Sea Research Part I: Oceanographic Research 91 (2014) 36-49. [21] M. Mueller, J. Pander, J. Geist, The effects of weirs on structural stream habitat and biological communities, Journal of Applied Ecology 48 (6) (2011) 1450-1461. [22] M. Schratzberger, K. Warr, S.I. Rogers, Patterns of nematode populations in the southwestern North Sea and their link to other components of the benthic fauna, Journal of Sea Research 55 (2006) 113–127. [23] M. Moreno, G. Albertelli, M. Fabiano, Nematode response to metal, PAHs and organic enrichment in tourist marinas of the mediterranean sea, Marine Pollution Bulletin 58 (8) (2009) 1192-1201. [24] A.S. Alves, H. Adão, T.J. Ferrero, J.C. Marques, M.J. Costa, J. Patrício, Benthic meiofauna as indicator of ecological changes in estuarine ecosystems: the use of nematodes in ecological quality assessment, Ecological Indicators 24 (2013) 462-475. [25] M. Moreno, F. Semprucci, L. Vezzulli, M. Balsamo, M. Fabiano, G. Albertelli, The use of nematodes in assessing ecological quality status in the Mediterranean (2) (2011) 328-336.